MIDWIFERY CARE FOR MRS. D IN A VILLAGE, SUB-DISTRICT INGIN JAYA, THE DISTRICT OF ACEH BESAR - Shafira, Richa; Sabrida, Oktalia; Lajuna, Lia (Journal of Midwifery and Community Health (JMCH), 2025)
Maternal and child health issues are crucial issues in healthcare because they directly impact the quality of future generations. One of the leading indicators of a country's health is the Maternal Mortality Rate (MMR). A high MMR indicates low-quality maternal healthcare services, including suboptimal antenatal care (ANC). Indonesia still faces challenges in reducing MMR, particularly in areas such as Aceh Besar Regency, which has a high maternal mortality rate. The purpose of this case report is to provide midwifery care for Mrs. D in Ajee Cut Village, Ingin Jaya District, Aceh Besar Regency, and document the results in a SOAP (Social Action Plan). The first care was provided on February 14, 2025. After data collection, the mother complained of fatigue. The examination results indicated that the mother's and fetus's conditions were within normal limits. Based on the analysis, the mother, a G2P1A0 woman at 34 weeks and 5 days of gestation, was in good condition. The care provided included education on the causes of the complaints, how to manage them, nutritional needs during the third trimester, and danger signs of pregnancy. The mother demonstrated a good understanding and was willing to follow the recommendations. Follow-up care will be provided at the next visit according to the needs and development of the mother's pregnancy.